2020
DOI: 10.21203/rs.3.rs-51671/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic Factors on Low-Birth-Weight Infants of Atresia and/or Tracheoesophageal Fistula: a Cohort Study

Abstract: Background: Low-birth-weight is the main factor affecting the survival rate of esophageal atresia (EA)/ tracheoesophageal fistula (TEF). The study aims to summarize the factors influencing the prognosis of EA/TEF, which is expected to be helpful for clinical diagnosis and treatment. Methods: A retrospective data analysis was performed in our hospital underwent TEF/EA repair between January 2012 and January 2015. The incidence of preoperative, intraoperative critical events and postoperative complications and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Research in China in 2020 entitled Prognostic Factors on Low-Birth-Weight Infants of Atresia and / or Tracheoesophageal Fistula: a Cohort Study, with a study sample of 81 patients, found that the overall prevalence of preoperative, intraoperative, and postoperative complications was significantly higher in lowbirth-weight patients (P = 0.002, P = 0.001, P = 0.001), but OS was lower (75.9 percent vs 92.3 percent, p = 0.027). The postoperative OS of patients with stress hyperglycemia was lower than that of patients with euglycemia (81.0 percent vs 93.6 percent, p = 0.03) [28] . Another study in India in 2008, entitled Esophageal atresia: Factors influencing survival -Experience at an Indian tertiary center with a total sample size of 127 samples collected from February 2004 to May 2006, explained that In 117 cases, EA with TEF was the most common type (92 percent ).…”
Section: Resultsmentioning
confidence: 79%
“…Research in China in 2020 entitled Prognostic Factors on Low-Birth-Weight Infants of Atresia and / or Tracheoesophageal Fistula: a Cohort Study, with a study sample of 81 patients, found that the overall prevalence of preoperative, intraoperative, and postoperative complications was significantly higher in lowbirth-weight patients (P = 0.002, P = 0.001, P = 0.001), but OS was lower (75.9 percent vs 92.3 percent, p = 0.027). The postoperative OS of patients with stress hyperglycemia was lower than that of patients with euglycemia (81.0 percent vs 93.6 percent, p = 0.03) [28] . Another study in India in 2008, entitled Esophageal atresia: Factors influencing survival -Experience at an Indian tertiary center with a total sample size of 127 samples collected from February 2004 to May 2006, explained that In 117 cases, EA with TEF was the most common type (92 percent ).…”
Section: Resultsmentioning
confidence: 79%